The Effect of Trust and Service Quality on Customer Satisfaction at Emersia Hotel & Resort Batusangkar - Safhira, Sahda; Suyuthie, Hijriyantomi (Journal of Multidimensional Management, 2025)
The hospitality industry plays a pivotal role in driving tourism development and regional economic growth, where trust and service quality are widely recognized as fundamental determinants of customer satisfaction. In the face of intensifying global competition and the proliferation of digital booking platforms, hotels are required to ensure not only adequate physical facilities but also consistent, responsive, and reliable service delivery to sustain guest loyalty. This study aims to examine the effect of trust and service quality on customer satisfaction at Emersia Hotel & Resort Batusangkar. A quantitative research design with a causal-associative approach was employed, involving 110 respondents selected through purposive sampling. Data were collected using a structured questionnaire with constructs of trust, service quality, and customer satisfaction, and analyzed using SPSS version 25 through validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The findings indicate that both trust and service quality have a positive and significant effect on customer satisfaction, with an adjusted R² of 0.510, showing that these two variables jointly explain 51% of the variance in satisfaction. The results highlight that improvements in staff competence, responsiveness, and assurance are critical strategies for strengthening guest trust and ensuring sustained competitiveness. This study contributes to the hospitality management literature by providing empirical insights into the determinants of customer satisfaction in a regional hotel context, while offering practical implications for hotel managers seeking to enhance service excellence and long-term customer loyalty.